2015
DOI: 10.1116/1.4919736
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured thin films for hydrogen-permeation barrier

Abstract: The authors confirmed that applying a coating of Al2O3, TiC, or TiN on a substrate reduced the hydrogen permeation by a factor of at least one order of magnitude compared with uncoated substrates. Al2O3 films consisting of fine crystal grains, with diameters of about 40 nm or less, provided superior hydrogen-permeation barriers on the test specimens. The test specimens coated with TiN or TiC films, with columnar crystals grown vertically on the substrate, tended to exhibit higher hydrogen permeability. The mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 47 publications
(88 reference statements)
2
25
0
Order By: Relevance
“…These treatments must be applied in an accurate manner; in fact the coating process itself can introduce hydrogen [109]. 211,238]. Nitriding of the parent material's surface layer has been successfully used in various austenitic stainless steels in order to limit hydrogen ingress [130,137].…”
Section: Hydrogen Embrittlement Mitigation Strategies and Design Of Nmentioning
confidence: 99%
See 1 more Smart Citation
“…These treatments must be applied in an accurate manner; in fact the coating process itself can introduce hydrogen [109]. 211,238]. Nitriding of the parent material's surface layer has been successfully used in various austenitic stainless steels in order to limit hydrogen ingress [130,137].…”
Section: Hydrogen Embrittlement Mitigation Strategies and Design Of Nmentioning
confidence: 99%
“… in particular has been shown to reduce wear [172]; thus, this coating may be particularly useful in bearing applications. Other compounds, such as [12], and have been proposed [56, 211, 238]. Nitriding of the parent material’s surface layer has been successfully used in various austenitic stainless steels in order to limit hydrogen ingress [130, 137].…”
Section: Hydrogen Embrittlement Mitigation Strategies and Design Of Nmentioning
confidence: 99%
“…It has been found out that the most efficient barriers to hydrogen penetration are ultrafine-grained coatings without columnar structure [21,22]. Hydrogen penetration in these coatings decreases by two orders of magnitude as the grain size decreases from 100 to 20 nm [21,22]. The results reported by Tamura et al [22] showed that nanostructured titanium nitride is more efficient compared to nanostructured TiC and Al 2 O 3 .…”
Section: Introductionmentioning
confidence: 96%
“…The results of a study of hydrogen permeability through different-type coatings on titanium alloys and other materials allowed identifying several common factors affecting the efficiency of these coatings. It has been found out that the most efficient barriers to hydrogen penetration are ultrafine-grained coatings without columnar structure [21,22]. Hydrogen penetration in these coatings decreases by two orders of magnitude as the grain size decreases from 100 to 20 nm [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…They are produced by various techniques: electrolytic deposition of metals and alloys, vacuum evaporation with subsequent condensation on the cathode substrate, the method of gas transport reactions, ion implantation, chemical-thermal treatment, etc. The composition of coatings is also very diverse: oxides, borides, nitrides, carbides, silicides [6][7][8][9][10][11][12]. Besides, many researchers are inclined to believe that it is more promising not to apply a certain coating, but to modify the surface, for example, using a pulsed carbon ion accelerator [13], or by means of high-energy methods, namely laser irradiation in various gas environments [14].…”
Section: Introductionmentioning
confidence: 99%